Spatial experience on tourism through MaaS (Mobility as a Service): Applying for a conjoint model of portfolio choice. Issue 3 (May 2023) - Kim, Hyunmyung; Lee, Kyuil; Joh, Chang-Hyeon; Kim, Jinhee; Moon, Sangmi; Lee, Changseok; Lee, Seungwoon; Lee, Jun; Lim, HyungJoo
Highlights: Spatial experience on tourism through MaaS (Mobility as a Service): applying for a conjoint model of portfolio choice. Decoupling theory decomposes tourist preference for tour travel into stages of MaaS. MaaS-conceptualized portfolios are clearly distinguished in their preference level. TaaS concept is needed as MaaS reveals the unique characteristics of tourism travel. Abstract: Travel significantly affects tourism and tourist satisfaction. Better tourism transport provision is essential to sustainable mobility and smart tourism. Knowing why tourists prefer specific travel alternatives is therefore important. Travel needs several trip stages over tourism space. Mobility as a Service (MaaS) offers alternatives to traveling to tourist attractions through various trip stages. The paper aims to show the relationships of the tourist preference for tourism travel alternatives represented as MaaS portfolios with MaaS provision of tourism destinations. To this end, the paper analyzes conjoint choices of tourism travel portfolios using a mixed logit model, evaluates the resultant willingness to pay (WTP)-based travel service preferences for 10 locally most visited cities of Korea, and compares the evaluations with the physical levels of MaaS provision of those cities. The preference for travel is found unique for tourism, and the tourists' evaluation of travel services has subtle differences from the MaaS provision level.